Natural Medicines for the Treatment of Epilepsy: Bioactive Components, Pharmacology and Mechanism - He, Li-Ying; Hu, Mei-Bian; Li, Ruo-Lan; Zhao, Rong; Fan, Lin-Hong; He, Lin; Lu, Feng; Ye, Xun; Huang, Yong-liang; Wu, Chun-Jie (Frontiers in Pharmacology, 2021)
Epilepsy is a chronic disease that can cause temporary brain dysfunction as a result of sudden abnormal discharge of the brain neurons. The seizure mechanism of epilepsy is closely related to the neurotransmitter imbalance, synaptic recombination, and glial cell proliferation. In addition, epileptic seizures can lead to mitochondrial damage, oxidative stress, and the disorder of sugar degradation. Although the mechanism of epilepsy research has reached up to the genetic level, the presently available treatment and recovery records of epilepsy does not seem promising. Recently, natural medicines have attracted more researches owing to their low toxicity and side-effects as well as the excellent efficacy, especially in chronic diseases. In this study, the antiepileptic mechanism of the bioactive components of natural drugs was reviewed so as to provide a reference for the development of potential antiepileptic drugs. Based on the different treatment mechanisms of natural drugs considered in this review, it is possible to select drugs clinically. Improving the accuracy of medication and the cure rate is expected to compensate for the shortage of the conventional epilepsy treatment drugs.